Study on the Influence of Temperature on Ultrasonic Pressure Measurement Technology. Issue 1 (1st January 2022) - Zhang, Yuqing; Ming, Tingfeng; LI, Jing
Abstract: Ultrasonic pressure measurement is an advanced measurement technology, but it has a great influence on temperature. Aiming at the problem that the pressure of ultrasonic measurement pipeline is affected by temperature, the pipeline is modeled and simulated by finite element method. The ultrasonic transducer is used to transmit and receive sound waves. The time difference of sound waves received by the transducer under different temperatures is simulated to determine the corresponding sound velocity. The data is analyzed and processed to establish the mathematical model of sound velocity and temperature, The influence of temperature on pressure measurement is analyzed, which plays an important role in reducing the pressure error of ultrasonic measurement pipeline.